2015
DOI: 10.1111/vec.12338
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood transfusion in dogs with thoracic or abdominal hemorrhage: 25 cases (2007–2012)

Abstract: ABT is an adjunct to volume replacement in dogs with thoracic or abdominal hemorrhage secondary to vascular trauma, ruptured tumor, or anticoagulant rodenticide toxicosis. ABT may be used as bridge to definitive hemorrhage control, particularly when other blood products are not available or affordable. Complications may include hypocalcemia, prolonged coagulation times, and hemolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 32 publications
4
44
1
8
Order By: Relevance
“…Using an estimated blood volume of 90 mL/kg for dogs, the dog in this report was autotransfused approximately 58% of his blood volume in less than 3 hours, thus fitting the criteria for massive transfusion. Massive transfusion and autotransfusion have been associated with coagulopathy, hypocalcemia, and other electrolyte disturbances . Coagulopathy can occur due to dilution of platelets and clotting factors, or secondary to anticoagulants added to the donor blood.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Using an estimated blood volume of 90 mL/kg for dogs, the dog in this report was autotransfused approximately 58% of his blood volume in less than 3 hours, thus fitting the criteria for massive transfusion. Massive transfusion and autotransfusion have been associated with coagulopathy, hypocalcemia, and other electrolyte disturbances . Coagulopathy can occur due to dilution of platelets and clotting factors, or secondary to anticoagulants added to the donor blood.…”
Section: Discussionmentioning
confidence: 80%
“…An autotransfusion unit or cell salvage device was not available and thus autotransfusion was carried out by transferring the blood from the suction canister to an empty blood transfusion collection bag with a standard in‐line blood filter. Although the collected blood could contain red blood cell fragments, activated platelets, cytokines, bone fragments, and fat, previous studies in the veterinary and human literature have shown that the administration of unwashed blood is safe when administered through a filter …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of leucoreduction filters has shown to remove between 97.6 and 99 per cent of bacterial load and no autotransfusion infections have been identified 19. A veterinary study reported successful use of autotransfusion of filtered blood where trauma was the source of bleeding; no significant association between survival and aetiology of haemorrhage was found, and no autotransfusion infections were identified 20. Although not relevant to the orthopaedic case presented here, a controversy exists in autotransfusion of oncology patients; although cancer cells or their fragments have been found in salvaged blood, some authors question their ability to cause metastases 21.…”
Section: Discussionmentioning
confidence: 99%